Pengaruh Motivasi Kerja, Pelatihan Dan Pengembangan Sumber Daya Insani Terhadap Prestasi Kerja Karyawan Baitul Maal Wa Tamwil Di Kabupaten Tulungagung Dalam Perspektif Islam - Muhamad Ali Tamrin (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2021)
The development of baitul maal wa tamwil (BMT) in Tulungagung which of course must also be supported by adequate human resources, both in terms of quality and quantity. To achieve the goal of baitul maal wa tamwil, of course, employees are needed who are able to carry out their respective duties, as evidenced by optimal work performance. And to optimize the performance of the work, it takes motivation both from yourself and from outside, and it takes training and human resource development. Formulation of this research problem Does work motivation affect the work performance of baitul maal wa tamwil employees in Tulungagung district in an Islamic perspective? whether the training affects the work performance of baitul maal wa tamwil employees in Tulungagung district in an Islamic perspective; does the development of human resources affect the work performance of baitul maal wa tamwil employees in Tulungagung district in an Islamic perspective? Does the motivation of work, training, and human resource development jointly affect the work performance of baitul maal wa tamwil employees in Tulungagung district in an Islamic perspective? Furthermore, this study aims: To test the influence of motivation, the influence of training, the influence of human resource development on the work performance of baitul maal wa tamwil employees in Tulungagung Regency; In addition, it aims to jointly test the influence of motivation, training, and human resource development on the work performance of baitul maal wa tamwil employees in Tulungagungaung Regency from the results of research can be concluded: There is a significant influence together from work motivation, training, human resource development on the work performance of Baitul Maal wa Tamwil employees in Tulungagung district.